Om Grundtvigs poetik med særligt henblik på den bibelske inspiration - Thodberg, Christian (Grundtvig-Studier, 1982)
On Grundtvig’s Poetics, with particular reference to the Biblical inspiration By Christian Thodberg This paper is, in slightly adapted form, Professor Thodberg’s official opposition to the defence of the dissertation The Active Word by Lektor Flemming Lundgreen-Nielsen for the degree of Doctor of Philosophy. Thodberg calls the book an impressive scientific contribution. Its sub-title explains that it deals with “Grundtvig’s Poetry, Literary Criticism and Poetics 1798-1819”, and that it will for many years to come be the handbook on and introduction to the first part of Grundtvig’s work. However, all who are aware of the difficulties of Grundtvig research must question whether it really does meet the demand for an exhaustive treatment that the author himself emphasizes as being its “main aim”. The author rejects the line of “existential” research taken by, for example, Aage Henriksen and Jørgen Elbek, and defines his work as documenting and verifying areas of the transmitted “text-corpus” in the tradition of Helge Toldberg and Gustav Albeck. The author is also one of the few remaining classically- trained academics capable of producing such a work. But does the book have a thesis? This is not made clear in the introduction and in fact only becomes apparent towards the end: Grundtvig regarded himself as a symbol of an approaching renaissance in Scandinavia. The author argues for this “self-symbolism” via psychology, the history of ideas, literature, politics, theology and religion (p. 885-6). One wishes that the rest of the book had been written in the same vein as this concluding description of Grundtvig’s development. The book’s title is a thesis, too; but it cannot be said to have been argued in the contents. Is the self-symbolism incorporated into the book as a driving-force behind it, and therefore substantiated? In the English summary at the end of the book nofewer than four theses are put forward, only one of which is accepted by Thodberg, namely, that of self-symbolism. The outer framework, that is, the limitation to the period 1798-1819, is determined however by a consideration very different from the concluding thesis, namely, by Grundtvig’s relationship to the contemporary literary world and his liberation from contemporary literary norms. The dissertation ought to have been tightened up considerably, and then broadened to include a longer time-span. The epilogue shows that the author could have achieved this. For there, speaking of “N ew Year’s Morn” 1824, he writes that this poem “is the culmination of Grundtvig’s self-symbolism”, “the total liberation from current ideas about poetry”. And with regard to his relationship to his literary contemporaries, Grundtvig’s “Literaire Testament” 1827 should have been respected as the date to stop at. To a certain extent the author acknowledges this (p. 861 and 879), and quite rightly so. In 1827 Grundtvig achieved the state of clarity that set him decisively on his own road. The first volume is the most fully-formed. Here Grundtvig’s romantic attitude and its relationship to Christianity is soundly and convincingly demonstrated by virtue of the author’s knowledge and penetrating analytical method. In the second volume the amount of material expands enormously and the author’s treatment thus becomes somewhat summary here and there. Any interpreter must increasingly come to understand Grundtvig on his own terms. It is presumably here that the author sees the danger in the existential approach. But Professor Thodberg cannot see how the author can avoid moving into its orbit. He is still using the tools of literary history, but they are not adequate to the task. A major example of the limitations of this method of approach is the author’s treatment of Lovely is the Clear, Blue Night, where the children in the poem are made into a framework, a “fiction”, and the author searches through literature tofind support for “the waving stars” in the poem. The answer is, they belong to Grundtvig’s N ew Year’s poems, in which they have a guiding role. In this hymn, just as in A Child is Born in Bethlehem (1820) and O Welcome Again (1824) we find two levels, a duality which the author does not realise. It may well be children that we sing about, but the hymn is about adults, who must become like children again. Compared with the two other World Chronicles (1812 and 1817) Grundtvig’s World Chronicle 1814 receives unfavourable treatment, even though it is here that the author obtains his final thesis (“the active word”), actually from Grundtvig’s explanation of the particular character of the verb in Hebrew. It is a significant quotation from the book that the author calls attention to in his conclusion; but one wonders why he did not make far more use of WC 1814 and the linguistic articles in the journal Dane-Work (Danne-Virke) to justify the term “the active word”, and to set out Grundtvig’s poetics in general. According to Thodberg the major shortcoming in the dissertation is the lack of a thorough treatment of the sermons - not just because he himself is a theologian, but because it is precisely in the sermons that Grundtvig’s imagery and poetics are developed in practice. They may be said toform a bridge to the later hymns. The author quite rightly focuses on the sermon for Whit Monday 1813 because of its use of nature imagery, and he refers to the Whitsun sermon Grundtvig gave on June 6th 1824. Speaking of Grundtvig’s preaching style he says (p. 597) that it “corresponds ... in its rejection of norms and external rules ... to Grundtvig’s poetics”. Thus the author aligns the sermons and the poetry itself here, though Thodberg cannot see that the author makes a serious attempt to document the equality. In a manuscript quoted by the author Grundtvig says that “in euphonious prose a hidden metre is always present”, and Thodberg takes this sentence as his starting-point for a brief survey of Grundtvig’s sermons in Udby 1811-13 - as a necessary supplement to the book’s impoverished treatment and its concerns in general. The poetic tone breaks through in particular where Grundtvig is full of enthusiasm or in high spirits. At this point his prose takes on the character of poetry to such a degree that it can actually be set out as verse. Grundtvig has done this himself in WC 1814 in the two rewritings of Biblical prose, which Thodberg has placed alongside the text from Christian VII’s Bible (W C 1814 p . 28 and p. 54). He goes on to quote a whole series of examples of the poetic style in the Udby Sermons. Admittedly the author writes (p. 892): “The first-person symbolism makes its most significant mark in Grundtvig’s sermons”, and refers to the 1850’s. But in support of the author’s thesis a 12/13-page poetic sermon in the first-person form, from the First Sunday in Advent 1812 would have been a very powerful piece of evidence - on a par with the poem The Easter L ily . The first-person style is equally sustained in Grundtvig’s sermons for the Second and Third Sundays in Advent. Three Sundays in a row he breaks every conceivable rule and norm for the sermon form. In other words he already had implemented the breaking of norms that he had discussed in his manuscript from 1813. This violent outburst of self-awareness would also explain some important events in his life, such as his letters to J.P. Mynster and Christian Molbech on Dec. 1st and 2nd 1812. Thus the weightiest criticism of this dissertation is the strange distance the author maintains between himself and the Biblical poetry and Christian con93 ceptual world. One cannot approach Grundtvig with this anti-theological attitude without fatal consequences. It is hard to conceive how the author would treat Grundtvig’s hymns from a later period. The totality which the author stresses so strongly is not borne out in his treatment of Grundtvig, according to Professor Thodberg. An important perspective in Grundtvig’s authorship is missing.